A review of the preclinical and clinical studies on the role of the gut microbiome in aging and neurodegenerative diseases and its modulation - Hashim, Haslin Madihah; Makpol, Suzana (Frontiers in Cellular Neuroscience, 2022)
As the world population ages, the burden of age-related health problems grows, creating a greater demand for new novel interventions for healthy ageing. Advancing ageing is related to a loss of beneficial mutualistic microbes in the gut microbiota caused by extrinsic and intrinsic factors such as diet, sedentary lifestyle, sleep deprivation, circadian rhythms, and oxidative stress, which emerge as essential elements in controlling and prolonging the life expectancy of healthy ageing. This condition is known as gut dysbiosis, and it affects normal brain function via the brain-gut microbiota (BGM) axis, which is a bidirectional link between the gastrointestinal tract (GIT) and the central nervous system (CNS) that leads to the emergence of brain disorders such as Alzheimer’s disease (AD), Parkinson’s disease (PD), amyotrophic lateral sclerosis (ALS), and frontotemporal dementia (FTD). Here, we reviewed the role of the gut microbiome in ageing and neurodegenerative diseases, as well as provided a comprehensive review of recent findings from preclinical and clinical studies to present an up-to-date overview of recent advances in developing strategies to modulate the intestinal microbiome by probiotic administration, dietary intervention, faecal microbiota transplantation (FMT), and physical activity to address the ageing process and prevent neurodegenerative diseases. The findings of this review will provide researchers in the fields of ageing and the gut microbiome design innovative studies that leverage results from preclinical and clinical studies to better understand the nuances of ageing, gut microbiome, and neurodegenerative diseases.